Integration of graph theory and matrix approach with fuzzy AHP for equipment selection - Hossein Safari; Alireza Faghih; Mohammad Reza Fathi (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: The purpose of this paper is applying a new integrated method to equipment selection. Design/methodology/approach: In this paper, we proposed the new integrated approach. Proposed approach is based on fuzzy Analytic Hierarchy Process (FAHP) and GTMA (graph theory and matrix approach) methods. FAHP method is used in determining the weights of the criteria by decision makers and then rankings of equipments are determined by GTMA method. Proposed approach is applied to a problem of selecting CNC machines to be purchased in a company. Findings and Originality/value: The outcome of this research is ranking and selecting equipment using of Fuzzy AHP and GTMA techniques. Originality/value: This paper offers a new integrated method for equipment selection.
Keywords: 650; graph theory and matrix approach; analytic hierarchy process; fuzzy Set; equipment selection